Effects of Upper and Lower Limb Plyometric Training Program on Components of Physical Performance in Young Female Handball Players - Hammami, Mehrez; Gaamouri, Nawel; Suzuki, Katsuhiko; Shephard, Roy J.; Chelly, Mohamed Souhaiel (Frontiers in Physiology, 2020)
Purpose This study examined the effects of a 10-week combined upper and lower limb plyometric training (ULLPT) programs on components of physical performance in young female handball players. Methods Participants aged 15.8 ± 0.2 years were randomly assigned between the experimental (EG; n = 17) and control (CG; n = 17) groups. Two-way analyses of performance (group × time) assessed changes in handgrip force, back extensor strength; medicine ball throwing, 30-m sprint times, change of direction (CoD) [Modified Illinois test (Illinois-MT)], four jumping tests [squat jump (SJ), countermovement jump (CMJ), CMJ with arms (CMJA) and 5 jump test (5JT), static and dynamic balance, and repeated sprint T-test scores (RSTT)]. Results After 10 weeks of plyometric training (two sessions per week), group × time interactions showed significant changes in EG relative to CG in right and left handgrip force, back extensor strength and medicine ball throwing [p < 0.001, d = 1.51 (large); p < 0.0001, d = 0.85 (large); p < 0.001, d = 0.90 (large); p < 0.0001, d = 0.52 (medium), respectively]. Group × time interactions also showed improvements of EG relative to CG in sprint times [5 m (p = 0.02, d = 0.80 (large)); 10 m (p < 0.0001, d = 1.00 (large)); 20 m (p = 0.02, d = 1.41 (large)); and 30 m (p = 0.02, d = 2.60 (large))], CoD [Illinois-MT (p < 0.001, d = 1.58 (large))] and jumping [(SJ, CMJ, CMJA, and 5JT, p = 0.001, d = 0.87 (large); p < 0.001, d = 1.17 (large); p < 0.001, d = 1.15 (large); and p = 0.006, d = 0.71 (medium)) respectively]. Further, all RSTT scores (best time, mean time, total time, and fatigue index) improved significantly in the experimental group, with group × time interactions varying between p < 0.001 and p = 0.049 (d value large to medium). However, balance did not differ significantly between EG and CG. Conclusion We conclude that 10 weeks of ULLPT improved many measures of physical performance in young female handball players.